2007
DOI: 10.1111/j.1365-2958.2007.06054.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Dr adhesins of Escherichia coli to carcinoembryonic antigen triggers receptor dissociation

Abstract: SummaryCarcinoembryonic antigen (CEA)-related cell adhesion molecules (CEACAMs) are host receptors for the Dr family of adhesins of Escherichia coli. To define the mechanism for binding of Dr adhesins to CEACAM receptors, we carried out structural studies on the N-terminal domain of CEA and its complex with the Dr adhesin. The crystal structure of CEA reveals a dimer similar to other dimers formed by receptors with IgVlike domains. The structure of the CEA/Dr adhesin complex is proposed based on NMR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
90
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 38 publications
10
90
0
Order By: Relevance
“…Also, upon further inspection of the crystal structure that led to the suggestion of an ABED dimer, a GFCCЈCЉ dimer interface can also be found when molecules in adjacent unit cells are examined. This, along with the observation of similar GFCCЈCЉ dimers for E. coli expressed material for CEACAM5 (48) and CEACAM6 (49), supports our observation of a GFCCЈCЉ dimer for CEACAM1 in solution.…”
Section: Discussionsupporting
confidence: 75%
“…Also, upon further inspection of the crystal structure that led to the suggestion of an ABED dimer, a GFCCЈCЉ dimer interface can also be found when molecules in adjacent unit cells are examined. This, along with the observation of similar GFCCЈCЉ dimers for E. coli expressed material for CEACAM5 (48) and CEACAM6 (49), supports our observation of a GFCCЈCЉ dimer for CEACAM1 in solution.…”
Section: Discussionsupporting
confidence: 75%
“…Plasmid pCC90 was used as the template to introduce a stop codon at codon position 31 of DraD by site-directed mutagenesis, using a QuikChange kit as directed by the manufacturer (Stratagene). The resulting expressed peptide would include the signal peptide and only five amino acids of (33). Recombinant E. coli expressing NfaE was also constructed in our previous study (32).…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies have not directly addressed the role of adhesin recognition of CEACAM receptors in E. coli internalization. It has been demonstrated that CEACAM receptors are involved in Neisseria gonorrhoeae and Neisseria meningitidis internalization by epithelial cells (4,23,40), and Dr adhesins recognize the same CEACAM domains as the neisseriae (33).…”
mentioning
confidence: 99%
“…The homodimerization of CEACAM N-terminal IgV domains, in particular those of CEACAM1 and CEACAM5, has been described previously (18,19). However, the molecular mechanisms by which CEACAMs can heterodimerize have yet to be elucidated.…”
mentioning
confidence: 97%
“…One function of CEACAMs is cell adhesion (10). CEACAMs achieve this primarily through the N-terminal IgV domain, which can dimerize either through homo-or heterophillic interactions (18)(19)(20). Dimerization of CEACAMs can be either in cis or in trans, with the latter allowing for cell-cell adhesion (21,22).…”
mentioning
confidence: 99%